Renewable energy system at shipyard - Pulkkanen, Rasmus (My University, 2024)
The use and integration of renewable energy sources into business operations is becoming more common and their integration in the maritime industry will be essential in the future. Making this change voluntarily while being one of the leaders in the industry can further strengthen a company's reputation and competitive position, and also access to subsidies and funding can also be improved. Through a comprehensive analysis of technological developments, and economic considerations, this thesis aims to provide useful insights into the implementation of renewable energy systems in shipyard environments. In this thesis, different solar and wind power systems were analysed under different scenarios, where electricity price, system price, system size and system location were variables. In addition to economic considerations, the social aspect of sustainability must be taken into account when designing renewable energy systems. Ultimately, the decision to invest in renewables reflects a commitment to both environmental sustainability and long-term business success in an increasingly environmentally aware world. The economic results did not reveal a situation where immediate investments are required, with the majority of results generating a payback time of more than 10 years. The results show that traditional horizontal wind power is more profitable than silicon solar panels or vertical wind power. However, the profitability of wind power is significantly affected by wind speed and only a slight change in wind speed could have a decisive impact on the final results. The values of levelized cost of energy for silicon solar panels were slightly below 10 cents/kWh regardless of the orientation or the angle of the panels, but with wind power values below 5 cents/kWh was reached.
Keywords: renewable energy, photovoltaics, wind power, shipyard, feasibility